Perbedaan Hasil Belajar Siswa yang Menggunakan Multimedia Interaktif dengan Buku Teks dalam Pembelajaran Biologi di SMA - Asrizal Wahdan Wilsa (Universitas Wiralodra, 2019)
Learning is a process that requires resources as a support in the success of learning. As an educator, teachers must be careful in choosing the learning resources needed by students, so that the learning process can be achieved according to the purpose of learning. But in fact, the learning that teachers do in schools is still not utilizing the media as an appropriate learning resource for students, especially in the understanding of abstract biological concepts that require supporting media for student learning. This study aims to describe differences in student learning outcomes that use interactive multimedia with textbooks in biology learning at senior high school. The method used in this study is quasi-experimental, with Control Group Pretest - Posttest Design. Population in this research is class XI-MIPA I and XI-MIPA II. Class XI-MIPA I as experimental class and class XI-MIPA II as control class. The data were obtained by using a multiple choice test instrument of 30 questions. Based on the results of the pretest and posttest it was found that the average value of the experimental class was greater than the control class. Based on these findings, it can be concluded that there are differences in student learning outcomes that use interactive multimedia with textbooks in biology learning at senior high school.